Strategi Bauran Pemasaran pada Toko Roti Maulana Genteng Banyuwangi (Program Studi Ilmu Administrasi Bisnis, 2022)
This study aims to determine, analyze and describe the marketing mix strategy at the Maulana Genteng Bakery. The marketing mix strategy implemented by the Maulana Genteng Bakery includes product, price, place and promotion. Maulana Bakery focuses its marketing activities on products, pricing, distribution and promotion methods. This study aims to determine the marketing mix strategy run by Maulana Bakery using a qualitative descriptive analysis method, namely by collecting data directly from the company by conducting observations and interviews according to the object of research. The results of this study indicate that the marketing mix strategy has an important role in marketing its products. Where the four marketing mixes support and complement each other, and have their respective roles. The owner of the Maulana Bakery must correctly implement the marketing mix strategy that is applied.